Immunomagnetic nanoparticle-based assays for detection of biomarkers - Park H (Dove Medical Press, 2013)
Hoyoung Park,1,2 Mintai P Hwang,1 Kwan Hyi Lee1,2 1Center for Biomaterials, Biomedical Research Institute, Korea Institute of Science and Technology, 2Department of Biomedical Engineering, University of Science and Technology, Seoul, Republic of Korea Abstract: The emergence of biomarkers as key players in the paradigm shift towards preventative medicine underscores the need for their detection and quantification. Advances made in the field of nanotechnology have played a crucial role in achieving these needs, and have contributed to recent advances in the field of medicine. Nanoparticle-based immunomagnetic assays, in particular, offer numerous advantages that utilize the unique physical properties of magnetic nanoparticles. In this review, we focus on recent developments and trends with regards to immunomagnetic assays used for detection of biomarkers. The various immunomagnetic assays are categorized into the following: particle-based multiplexing, signal control, microfluidics, microarray, and automation. Herein, we analyze each category and discuss their advantages and disadvantages. Keywords: magnetic, multiplex, signal control, microfluidics, microarrays, automation